2014
DOI: 10.1093/jac/dku303
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in atazanavir pharmacokinetics and associations with time to clinical events: AIDS Clinical Trials Group Study A5202

Abstract: Atazanavir clearance differed by sex. Females with fast clearance and males with slow clearance had increased risk of virological failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…Nevertheless, antiretroviral strategy and demographic data were not described in Fayet's study, raising questions about the reasons for such a difference compared with our study. Venuto et al reported a significant difference for total concentrations between male and female patients with HIV infection under ATV treatment, although this was not the case in our study, either for total or unbound concentrations. Although TDF is known to decrease ATV exposure , both total and unbound concentrations were not statistically different between patients with and without TDF co‐administration.…”
Section: Discussioncontrasting
confidence: 96%
“…Nevertheless, antiretroviral strategy and demographic data were not described in Fayet's study, raising questions about the reasons for such a difference compared with our study. Venuto et al reported a significant difference for total concentrations between male and female patients with HIV infection under ATV treatment, although this was not the case in our study, either for total or unbound concentrations. Although TDF is known to decrease ATV exposure , both total and unbound concentrations were not statistically different between patients with and without TDF co‐administration.…”
Section: Discussioncontrasting
confidence: 96%
“…In fact, most of the studies cited above had a much higher proportion of men than women. We are starting to appreciate the impact of sex on the safety and efficacy of cART 48,49 . But, similar to lessons learned from studying the independent impact of race on HIV outcomes 50 , a dedicated effort to specifically study the impact of sex on HIV outcomes must also be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-based differences in the pharmacokinetics, bioavailability, distribution, and metabolism of drugs have been reviewed [ 32 ] and differences in the clearance of ART have been described [ 111 ]. Factors such as body weight, fat distribution, intestinal absorption, protein binding and affinity, metabolism and excretion, and other metabolic functions differ between sexes [ 112 ] and might affect the distribution of the HIV reservoir within anatomic compartments.…”
Section: Discussionmentioning
confidence: 99%